KONFLIK KEJIWAAN TOKOH UTAMA DALAM NOVEL KORUPSI KARYA TAHAR BEN JELLEOUN (Psychological Conflict of The Main Character in Tahar Ben Jelleoun’s Novel, Korupsi) - nfn rahmawati (Kantor Bahasa Sulawesi Tenggara, 2017)
This study aims to describe main characters and psychological conflict experienced by the characters in “Korupsi” novel. The method used is qualitative descriptive method. Two issues are: (1) how the character of the character in “Korupsi” novel and (2) what psychological conflict experienced by the main character will be studied by combining a structural approach and psychological literature. The structural approach is used to understand the characterization aspect as one of the novel structures that discusses character and main figure’s character. The psychological literature is employed to understand psychological conflict and psychological problems experienced by the main characters. he results show that the main characters are easily tempted, inconsistent, impatient for having all his needs fulfilled. These characters makes him trapped in corruption case. The bribery money makes him in corruption trap in his office causes inevitable psychological conflicts. The main character decision to get involved in corruption case is inseparable from influence and pressure from family and his friends in his office. The action to neglect principle, integrity, and honesty that have been retained for many years causes him trapped in psychological conflicts. Psychological conflicts experienced by the main characters lead to psychological problem in the main characters, such as guilt, shame, negative hallucinations, nightmares, and desire to suicide.